Fecal microbial composition associated with testosterone in the development of Meishan male pigs - Jiang, Xueyuan; Deng, Shaoshan; Lu, Naisheng; Yao, Wen; Xia, Dong; Tu, Weilong; Lei, Hulong; Jia, Peng; Gan, Yeqing (Frontiers in Microbiology, 2023)
The gut microbiota closely relates to host health, whereas the relationship between gut microbiota and testosterone during the development of Meishan male pigs remains unclear. This study investigated the fecal microbiota composition and testosterone level during development in Meishan male pigs. Results showed that the fecal testosterone content increased significantly from 10 weeks (wk) to 22 wk of age (P < 0.05). Meanwhile, the boars at 22 wk had a lower abundance of phylum Bacteroidetes and Proteobacteria, and genus Alloprevotella, Prevotella_1, Prevotellaceae_NK3B31_group, and Streptococcus in the fecal microbiota composition (P < 0.05). but higher proportions of the phylum Actinobacteria, Firmicutes, Kiritimatiellaeota and Tenericutes, and genus Clostridium_sensu_stricto_1, Muribaculaceae and Terrisporobacter than that at 10 wk (P < 0.05), and the Firmicutes to Bacteroidetes ratio was higher at 22 wk than 10 wk (P < 0.05). Moreover, the fecal testosterone level significantly correlated with the relative abundance of the phylum Actinobacteria, Firmicutes, and Tencuteseri, and genus Alloprevotella, Clostridium_sensu_stricto_1, Muribaculaceae, Prevotella_1 and Streptococcus. Furthermore, the in vitro experiments indicated that the abundance of the phylum Proteobacteria and genus Escherichia-Shigella reduced with the increase of supplemental testosterone level. In contrast, the proportion of Firmicutes phylum increased with additional testosterone levels. These results provide us with new insights into the relationship between the gut microbiome and testosterone and the contributions of the gut microbiome in physiological regulation in response to gonad development.